Structural and thermoelectric properties of zn-doped cuprous aluminate delafossite - Wongcharoen, Ngamnit; Gaewdang, Thitinai; Wongcharoen, Tiparatana (My University, 2013)
The polycrystalline Zn-doped CuAlO2 ceramics were obtained by solid state reaction method. The mixture of high purity grade of CuO, Al2O3 and Zn(CH3COO) 2{dot operator}2H2O powders was ground and then pressed by using uniaxial pressure. The obtained pellet was sintered in air at 1,150 °C for 24 h. XRD patterns showed the crystal structure of the as-sintered CuAl1-xZnxO2 (0≤x≤0.05) belonging to rhombohedral, space group R3m along with the CuO and CuAl2O4 phases. From SEM micrographs, the grain size slightly decreases when the amount of Zn in CuAl1-xZnxO2 samples increases. Hall mobility and hole concentration of the as-sintered samples were obtained from Hall effect measurements in van der Pauw configuration at room temperature. The electrical resistivity measurements as a function of temperature were performed. The variation of Seebeck coefficient and power factor as a function of temperature was also investigated. In the present study, the Zndoped CuAlO2 ceramics probably have advantages for use in high temperature thermoelectric devices. © (2013)Trans Tech Publications,Switzerland.
Keywords: Power factor; Seebeck coefficient; Thermoelectric properties; Zn-doped CuALO2